Induction of salt tolerance in Brassica rapa by nitric oxide treatment - Bano, Atiyyah; Noreen, Zahra; Tabassum, Fariha; Zafar, Fizza; Rashid, Madiha; Aslam, Muhammad; Shah, Anis Ali; Shah, Adnan Noor; Jaremko, Mariusz; Alasmael, Noura; Abdelsalam, Nader R.; Hasan, Mohamed E. (Frontiers in Plant Science, 2022)
Salinity is one of the major plant abiotic stresses increasing over time worldwide. The most important biological role of nitric oxide (NO) in plants is related to their development and growth under abiotic conditions. The present experiment was conducted to study the effect of salt stress (0 and 100 mM) and NO (0 and 80 μM) on two different ecotypes of Brassica rapa (L.): PTWG-HL and PTWG-PK. The different growth attributes, biochemical and physiological parameters, and the mineral contents were examined. The results indicated increased hydrogen peroxide (H2O2), relative membrane permeability, malondialdehyde (MDA), and Na+ content and decreased plant biomass in both ecotypes (PTWG-PK and PTWG-HL) under salt stress. In contrast, NO treatment resulted in increased plant biomass, chlorophyll content, and total soluble proteins and decreased H2O2, relative membrane permeability, MDA, total phenolic content, catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), and Na+. The combined effect of salt stress and NO application increased the chlorophyll a content, total phenolic content, and total soluble proteins, but decreased H2O2, relative membrane permeability, MDA, and Na+. The response of carotenoids, anthocyanins, and K+, Ca2+, and Cl− ions varied in both ecotypes under all treatment conditions. The PTWG-PK ecotype showed maximum overall growth response with the application of NO. Henceforth, it is proposed that the molecular mechanisms associated with NO-induced stress tolerance in plants may be exploited to attain sustainability in agriculture under changing climate scenarios.